ChemInform Abstract: Phosphahelicenes in Asymmetric Organocatalysis: [3 + 2] Cyclizations of γ‐Substituted Allenes and Electron‐Poor Olefins. Issue 36 (September 2015) - Gicquel, Maxime; Zhang, Yang; Aillard, Paul; Retailleau, Pascal; Voituriez, Arnaud; Marinetti, Angela
Abstract The phosphahelicene (PHE) is employed as mixture of two epimers in a 3:2 ratio as catalyst for the synthesis of highly functionalized cyclopentene derivatives.